Visceral: Essays on Illness Not as Metaphor - Dolphin-Krute, Maia (punctum books, 2017)
Memoirs about being sick are popular and everywhere and only ever contribute to pop narratives of illness as a single event or heroic struggle or journey. Visceral: Essays on Illness as Metaphor is not that. Visceral, to the extent that it is a memoir, is a record not of illness but of the research project being sick became. While rooted firmly in critical disability and queer practices, the use of personal narratives opens these approaches up to new ways of writing the body-ultimately a body that is at once theoretical and unavoidably physical. A body where everything is visceral, so theory must be too. From the gothic networks of healthcare bureaucracy and hospital philanthropy to the proliferation of wellness media, off-label usage of drugs, and running off to live a life with, these essays move fluidly through theoretical and physical anger, curiosity and surprise. Arguing for disability rights that attend to the theoretical as much as the physical, this is Illness Not As Metaphor, Being Sick and Time, and The Body in Actual Pain as one. A sick body of text that is-and is not-in direct correspondence to an actual sick body, Visceral is an unrelenting examination of chronic illness that turns towards the theoretical only to find itself in the realms of the biological and autobiographical: because how much theory can a body take?